PROBLEM IDENTIFICATION OF STUDENT LEARNING DIFFICULTIES IN THE LEARNING PROCESS AT SCHOOL - Alvina Khairani; Rizka Nisa Aulia Sinaga; Siti Nurhaliza; Habib Sitorus (Yayasan Haiah Nusratul Islam, 2025)
This study aims to identify and analyze students' learning difficulties and the efforts teachers can undertake to address these issues in schools. The research employs a library research method with a descriptive qualitative approach, utilizing various literature sources such as scientific journals, books, articles, and academic documents. Data were analyzed using content analysis to identify internal and external factors influencing students' learning difficulties. The findings reveal that students' learning difficulties are caused by internal factors such as mental maturity, intelligence level, motivation, and interest, as well as external factors such as family environment, community, teaching methods, and the availability of teaching aids. These difficulties hinder students' comprehension of learning materials, leading to a decline in academic achievement. Efforts to overcome learning difficulties involve the active role of teachers through identification, diagnosis, action planning, and support provision. Teachers apply approaches such as individual guidance, remedial programs, and the use of varied teaching methods, including relating materials to daily life. Additionally, teachers create a conducive learning environment and provide motivation to students. This study offers valuable insights for teachers and schools in designing learning strategies that support students' academic success.